Hermeneutika Yuridis: Diskriminasi Terhadap Prospek Kerja Sarjana Hukum Syariah - Munib, ABD MUNIB; Abd. Muni (TERAJU: Jurnal Syariah dan Hukum, 2023)
The aim of this research is to interpret the phrases contained in Law Number 49 of 2009 concerning General Justice Article 14 paragraph 1 letter d and Law Number 50 of 2009 concerning Religious Courts Article 13 paragraph 1 letter e which in its application is considered to discriminate against employment opportunities for law graduates sharia. The research method used is an interpretive qualitative method with a juridical hermeneutic approach. Juridical hermeneutics is a method of interpretation that takes into account the text, social context and historical context. Data analysis in this research was carried out by interpreting the phrases of the two laws. The research results show that Law Number 49 of 2009 and Law Number 50 of 2009 have ambiguous meanings which result in discrimination. Where sharia law graduates cannot work in the District Court or District Prosecutor's Office because they are deemed not to meet the qualifications. Meanwhile, a general law graduate is considered to meet the requirements to work at the Ministry of Religion.